2015
DOI: 10.1155/2015/340246
|View full text |Cite
|
Sign up to set email alerts
|

Time Savings and Surgery Task Load Reduction in Open Intraperitoneal Onlay Mesh Fixation Procedure

Abstract: Background. This study assessed the reduction in surgeon stress associated with savings in procedure time for mechanical fixation of an intraperitoneal onlay mesh (IPOM) compared to a traditional suture fixation in open ventral hernia repair. Study Design. Nine general surgeons performed 36 open IPOM fixation procedures in porcine model. Each surgeon conducted two mechanical (using ETHICON SECURESTRAPTM Open) and two suture fixation procedures. Fixation time was measured using a stopwatch, and related surgeon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
(42 reference statements)
0
9
0
1
Order By: Relevance
“…Surgeons agree that improved endoscopic linear stapling device stability is a critical component of surgery and is likely to result in more frequent positive surgical outcomes 33 . This could potentially reduce surgery stress based on the interesting theoretical framework of the biopsychosocial model (BPSM) of challenge and threat 34 that has been applied to explain differences in stress reaction to surgical device use 35 . The framework is predicated upon the surgeon's evaluation of the demands of a procedure compared against the possession or availability of necessary resources to cope effectively with such demands 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons agree that improved endoscopic linear stapling device stability is a critical component of surgery and is likely to result in more frequent positive surgical outcomes 33 . This could potentially reduce surgery stress based on the interesting theoretical framework of the biopsychosocial model (BPSM) of challenge and threat 34 that has been applied to explain differences in stress reaction to surgical device use 35 . The framework is predicated upon the surgeon's evaluation of the demands of a procedure compared against the possession or availability of necessary resources to cope effectively with such demands 34 .…”
Section: Discussionmentioning
confidence: 99%
“…These results support the results observed in a previous study, which demonstrated reductions in surgeon stress measured by SURG-TLX and faster fixation times. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Surgical task load was measured using the surgical task load index (SURG-TLX), a validated self-reported questionnaire that measures intraoperative mental stress and workload by evaluating six different dimensions: mental demands, physical demands, temporal demands, task complexity, situation stress, and distractions. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roy S. и соавт. (2015) [62] изучали снижение хирургического стресса, связанного с экономией времени при использовании механических сшивающих устройств по сравнению с ручными швами. Механические методы показали сокращение времени операции на 89,1 % по сравнению с ручным швом (p<0,00001), хирургический стресс был на 55 %, соответственно, ниже при его оценке по SURGTLX.…”
unclassified